2006
DOI: 10.1080/0906471051003087
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of cadmium (Cd++) on metabolism of sunflower (Helianthus annuusL.) seedlings

Abstract: Effects of cadmium chloride (CdCl 2 H 2 O) on the content of chlorophyll (a'/b), chlorophyll a/b ratio, proline, protein and abscisic acid in sunflower (Helianthus annuus L.) seedlings has been investigated. One-week-old seedlings were grown at cadmium concentration of 0.05, 0.07 and 0.09 mM for ten days in Hoagland's solution. Elevated cadmium levels increased the abscisic acid contents in roots, shoots and leaves of seedlings. An increase of proline in the leaves of seedlings exposed to cadmium occurred, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 32 publications
(22 reference statements)
8
13
0
Order By: Relevance
“…It should be also stressed that despite a reduction in the photosynthetic pigment content and leaf dry weight for the duration of the experiment, the M. jalapa plants yielded seeds at the end of their vegetative cycle. A decrease in chlorophyll content in plant stressed by heavy metals exposure was also been reported for other hyperaccumulators such as Helianthus annuus (Zengin and Munzuroglu 2006) and Brassica juncea (John et al 2009). …”
Section: Discussionsupporting
confidence: 60%
“…It should be also stressed that despite a reduction in the photosynthetic pigment content and leaf dry weight for the duration of the experiment, the M. jalapa plants yielded seeds at the end of their vegetative cycle. A decrease in chlorophyll content in plant stressed by heavy metals exposure was also been reported for other hyperaccumulators such as Helianthus annuus (Zengin and Munzuroglu 2006) and Brassica juncea (John et al 2009). …”
Section: Discussionsupporting
confidence: 60%
“…Osuocha et al, [10] reported that these decline in chlorophyll content under heavy metal stress is believed to be due to inhibition of important enzymes α-aminolevulic acid and protochlorophyllide reductase associated with chlorophyll biosynthesis. Similar decrease in chlorophyll under heavy metal stress was reported in Brassica Juncea L. [25], in sun flower [26], in Cucurbita pepo [10] and in almond [27]. Table 3 Table 3.shows the vitamin content of selected vegetables from Ishiagu as influenced by quarry effluent discharge.…”
Section: Discussionsupporting
confidence: 71%
“…The table 5 shows that proline content was highly affected with the CdCl 2 concentration. In higher plants, proline is accumulated under stress, both due to an increase in production by reducing its degradation [21], [6] .The accumulation of proline occurs after the development of resistance is a consequence rather than a cause of hardening [14]. In the present study proline increased significantly in the cadmium treated pea plants.…”
Section: B Chlorophyll Contentsupporting
confidence: 48%
“…In the present study proline increased significantly in the cadmium treated pea plants. Enhanced proline accumulation in reponse to Cd toxicity has been earlier demonstrated in Triticum aestivum, Vigna radiate, Helianthus annus and Phaseolus vulgaris [10], [6], [13]Thus, proline accumulation is a potential indicator of stress tolerance [12]. Proline also acts directly as an antioxidant to protect the cell from free radical damage and maintains a more reducing environment that is favorable for phytochelation synthesis and cadmium sequestration [8], [5] .…”
Section: B Chlorophyll Contentmentioning
confidence: 99%